PENERAPAN METODE MINDMAPPING MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SMAN 1 KUTA UTARA - Jeslie Kartika Viani; I Gusti Agung Ngurah Trisna Jayantika (Widyadari, 2023)
Creative thinking can be one of the supports in the problem solving process. The mindmapping method can improve students' creative thinking skills, because with the Mind Mapping method it is more fun and students are active in the learning process and students are able to increase knowledge and come up with ideas in solving problems that arise in the learning process. This study aims to apply the mindmapping method to students' creative thinking abilities. This type of research is classroom action research with a research design from Kemmis & McTaggart. The research location was at SMAN 1 Kuta Utara with the subjects in this study being all students in class XI MIPA 3 with a total of 45 people. This research was conducted in biology subjects with excretory system material. The results showed that there was an increase in the ability to think creatively in cycle I by 68.8% and in cycle II by 86.7%. Based on the results of data analysis, it can be seen that the application of the mindmapping method can improve students' creative thinking skills, where the number of students who achieve completeness in cycle II reaches 86.7%.